1996
DOI: 10.1161/01.res.79.4.871
|View full text |Cite
|
Sign up to set email alerts
|

Mildly Oxidized LDL Evokes a Sustained Ca 2+ -Dependent Retraction of Vascular Smooth Muscle Cells

Abstract: Oxidized low density lipoprotein (LDL) is thought to play a major role in atherogenesis. Atherosclerotic arteries exhibit structural changes associated with profound alterations in vascular tone that are potentially involved in arterial spasm and ischemic heart disease. We report here the role of oxidized LDL in the retraction of vascular smooth muscle cells. Mildly oxidized LDL elicited a broad and sustained peak in cytosolic calcium concentration ([Ca2+]i) in cultured arterial smooth muscle cells. Concomitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…It has been reported that OxLDL stimulates a variety of signal pathways in several cell types, including the sphingomyelin-ceramide pathway (38), Ca-dependent signaling (39,40), protein kinase C (41), tyrosine kinase-dependent activation of ERK (19,20), and a p38 MAPK pathway (11). OxLDL can also activate PPAR␥-inducible gene expression, because the oxidized fatty acids contained in OxLDL, 13-hydroperoxyoctadecadienoic acid (13-HPODE) and 13-(S)-hydroxyoctadecadienoic acid (13-HODE), are ligands for PPAR␥ (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that OxLDL stimulates a variety of signal pathways in several cell types, including the sphingomyelin-ceramide pathway (38), Ca-dependent signaling (39,40), protein kinase C (41), tyrosine kinase-dependent activation of ERK (19,20), and a p38 MAPK pathway (11). OxLDL can also activate PPAR␥-inducible gene expression, because the oxidized fatty acids contained in OxLDL, 13-hydroperoxyoctadecadienoic acid (13-HPODE) and 13-(S)-hydroxyoctadecadienoic acid (13-HODE), are ligands for PPAR␥ (25).…”
Section: Discussionmentioning
confidence: 99%
“…by guest, on May 2, 2019 www.jlr.org Downloaded from move EDTA, then the nLDL fraction (0.2 mg/ml, diluted in PBS) was incubated with 5 mol/l CuSO 4 at 37 Њ C for 3 h. The reaction was stopped by adding EDTA (final concentration, 0.25 mmol/l). It is likely that such OxLDL has considerable amounts of peroxidized lipids.…”
Section: Preparation Of Native Low Density Lipoprotein and Oxldlmentioning
confidence: 99%
“…endothelial dysfunction, or by promoting smooth muscle cell proliferation. 23,[25][26][27][28] A recent study by Ramsey et al 29 showed that arterial distensibility is controlled by normal endothelium in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, oxidative modification of LDL is a key factor for progression of atherosclerosis [19], and in vitro application of oxidized LDL mimicked the abnormal vascular reactivity, which was seen in atherosclerotic artery [4,9,13]. Several studies suggested that LPC might be the active component mediating the in vitro effect of oxidized LDL on vascular contraction.…”
mentioning
confidence: 99%